The Management Business Hospitality Students' Competence in Using Past Tense - Jokosaharjo, Sulistyoadi; Paramita Sari, Ni Luh Komang Julyanti (Jurnal Manajemen Pelayanan Hotel, 2023)
In English, past tense is one of main tenses which is used in daily life. However, mastering it is not a simple matter. This study aims to find out students past tense mastery competence of the second-semester students of Management Business Hospitality of Triatma Mulya University before they get English Intermediate Course which mainly discuss past activities. Their past tense competence can be assessed by identifying the present and the number of errors which made by the students. The data was gathered by asking them to write down five sentences of their past activities. The subject was a class of second semester students of Management Business Hospitality in total of 21 students. The analysis was conducted by applying Ellis’ error categories of omission, misordering, and misinformation on each sentence of the students. Each sentence made by the students was analyzed to find out the present of each error category. The finding showed that the students had an insufficient competence in using past tense, in which, the major error was in form of misinformation error where the students tended to use present form instead of past form in retelling their past activities. The omission and misordering errors were the minor errors and not as significant as the misinformation error. Keywords: Past Tense Mastery, Competence, Omission, Misordering, Misinformation.